Algorithms as complementary abstractions - Matzner, Tobias (New media & society, 2024)
The text diagnoses two opposing tendencies in the research on algorithms: the first abstracts and unites heterogeneous developments under the term “algorithm”; the second emphasizes specifics such as data sets, material conditions, software libraries, interfaces, and so on, thus dissolving that which apparently algorithms do into more fine-grained analyses. The text proposes a research perspective that resolves this tension by conceiving of algorithms as a relation between the abstract and the concrete that allows to capture both in their interdependence. This approach is informed by two motives: first, the necessity to connect detailed analyses of specific information technologies with general political concerns; and second, the application of recent feminist critiques of epistemology to the analysis of algorithms. The ensuing relational perspective on algorithms is connected to the genealogy of algorithmic technology before being demonstrated regarding the mutually complementing relationships: algorithms-materiality, algorithms-data, algorithms-code, and algorithms-interfaces.